Emerging Biomarkers in Cancer Diagnosis and Prognosis - Hmod, Raghad Qutaba; Kadr, Zahraa Mohammed Sattar; Kareem, Hadeel Zuhair Abdul; Mahdi, Sabeha Khirallah (American Journal of Biomedicine and Pharmacy, 2025)
Biomarkers play a crucial role in cancer diagnosis and prognosis, enabling early detection, personalized treatment, and therapeutic monitoring. Despite significant advancements, challenges remain in identifying reliable, specific, and clinically applicable biomarkers. This study reviews recent developments in biomarker discovery, focusing on genomic, proteomic, and metabolomic markers, as well as the emerging role of liquid biopsies. Using a multidisciplinary approach, we analyze advancements in biomarker research, the integration of artificial intelligence for biomarker identification, and the implications for precision medicine. Findings suggest that novel biomarkers enhance diagnostic accuracy, improve treatment outcomes, and offer new opportunities for targeted therapies. The results highlight the need for further validation and standardization to ensure clinical reliability. This study underscores the potential of biomarkers to revolutionize cancer management and contribute to the future of precision oncology.